Following A Glittering Trail: Geo-Chemical and Petrographic Characterization of Micaceous Sherds Recovered from Dismal River Sites. Issue 2 (April 2016) - Trabert, Sarah; Eiselt, Sunday; Hill, David V.; Ferguson, Jeffrey; Beck, Margaret
Abstract: Protohistoric Ancestral Apache Dismal River groups (A.D. 1600–1750) participated in large exchange networks linking them to other peoples on the Plains and U.S. Southwest. Ceramic vessels made from micaceous materials appear at many Dismal River sites, and micaceous pottery recovered from the Central High Plains is typically seen as evidence for interaction with northern Rio Grande pueblos. However, few mineral or chemical characterization analyses have been conducted on these ceramics, and the term "micaceous" has been applied to a broad range of vessel types regardless of the form, size, or amount of mica in their pastes. Our recent analyses, including macroscopic evaluation combined with petrography and neutron activation analyses (NAA), indicate that only a small subset of Dismal River sherds are derived from New Mexico clays. The rest were likely manufactured using materials from Colorado and Wyoming. Seasonal mobility patterns may have given Dismal River potters the opportunity to collect mica raw materials as they traveled between the Central Plains and Front Range, and this has implications for the importance of internal Plains social networks during the Protohistoric and Historic periods.